2022
DOI: 10.1101/2022.05.30.493998
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The energy landscape reshaped by strain-specific mutations underlies the long-range epistasis in NS1 evolution of influenza A virus

Abstract: The mechanisms underlying how individual mutations affect the protein energy landscape are crucial for understanding how proteins evolve. However, predicting mutational effects remains challenging because of epistasis—the nonadditive interactions between mutations. Here, we investigate the biophysical mechanism of strain-specific epistasis in the nonstructural protein 1 (NS1) of the influenza A virus (IAV). To understand the molecular basis of epistasis, we conducted comprehensive analyses of four NS1s of IAV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Patterns of convergence are often offered as compelling evidence of adaptation and recent studies indicated that allosteric interactions in proteins not only dictate long-range couplings and signal transmission patterns but are also essential in the evolutionary adaptation of proteins. 134,135 It has been recognized that allosteric mechanisms regulate emergence and contribution of different conformational states and shape up functional landscapes, enabling evolutionary adaptation of new functions through controlled modulation of conformational plasticity. 135 We hypothesized that sites of convergent mutations target specific structural hotspot of adaptation that may be organized through engagement to the pre-existing allosteric network.…”
Section: Perturbation Response Scanning Reveals Complementary Role Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…Patterns of convergence are often offered as compelling evidence of adaptation and recent studies indicated that allosteric interactions in proteins not only dictate long-range couplings and signal transmission patterns but are also essential in the evolutionary adaptation of proteins. 134,135 It has been recognized that allosteric mechanisms regulate emergence and contribution of different conformational states and shape up functional landscapes, enabling evolutionary adaptation of new functions through controlled modulation of conformational plasticity. 135 We hypothesized that sites of convergent mutations target specific structural hotspot of adaptation that may be organized through engagement to the pre-existing allosteric network.…”
Section: Perturbation Response Scanning Reveals Complementary Role Of...mentioning
confidence: 99%
“…134,135 It has been recognized that allosteric mechanisms regulate emergence and contribution of different conformational states and shape up functional landscapes, enabling evolutionary adaptation of new functions through controlled modulation of conformational plasticity. 135 We hypothesized that sites of convergent mutations target specific structural hotspot of adaptation that may be organized through engagement to the pre-existing allosteric network.…”
Section: Perturbation Response Scanning Reveals Complementary Role Of...mentioning
confidence: 99%